(3YScQI GdeLJeY (B:s (3GdJCKjQGJ GdSjGSjI hGdCefjI (B/s - (3GdRdRdj, RjO MGRes ((3YeGf, GdCQOf (B:s (3OGQ CeLO ddfTQ h GdJhRjY (B:s (3EHUGQ fGTQhf hehRYhfs, 2017)
(3JTcd GdYScQI XGgQI eYQhaI aj MjGI GdTYhH hdG SjeG GdTYH GdYQGbj Ydi hLg GdJMOjO, MjK de Jcf GdYScQI ajg fJGL deG MUd HYO YGe (B2003 (3, Hd Ef gPg GdXGgQI HQRJ eYGdegG aj GdeLJeY GdYQGbj ef YGe (B1968 (3hHbjJ edGReI dg WjdI GdYbhO GdeGVjI, EdG CfgG JJUGYO hJfNaV habG deYGjjQ JNJda HGNJdGa GdeQMdI, aMjfG JQJHW HbhI GdSdWI hGdOhdI hGdYfa GdSjGSj GdeJQJH Ydi Pdc, hMjfG BNQ JXgQ HSHH VYa GdOhdI heDSSGJgG GdMchejI GdVGHWI, hYdi VhA Pdc jbOe gPG GdcJGH OQGSI Mhd YScQI GdeLJeY(B.s
(3HHdjhLQGajI (B: (3UaMI (B289-305s
Keywords: (3GdYQGbs -- (3SjGSI YScQjIs; (3GdYQGbs -- (3CMhGd GLJeGYjIs; (3GdYQGbs -- (3SjGSI hMcheIs